Large-scale survey of rates of achieving targets for blood glucose, blood pressure, and lipids and prevalence of complications in type 2 diabetes (JDDM 40) - Yokoyama, Hiroki (BMJ Open Diabetes Res Care, 2016)
OBJECTIVE: The fact that population with type 2 diabetes mellitus and bodyweight of patients are increasing but diabetes care is improving makes it important to explore the up-to-date rates of achieving treatment targets and prevalence of complications. We investigated the prevalence of microvascular/macrovascular complications and rates of achieving treatment targets through a large-scale multicenter-based cohort. RESEARCH DESIGN AND METHODS: A cross-sectional nationwide survey was performed on 9956 subjects with type 2 diabetes mellitus who consecutively attended primary care clinics. The prevalence of nephropathy, retinopathy, neuropathy, and macrovascular complications and rates of achieving targets of glycated hemoglobin (HbA1c) <7.0%, blood pressure <130/80 mm Hg, and lipids of low-density/high-density lipoprotein cholesterol <3.1/≥1.0 mmol/L and non-high-density lipoprotein cholesterol <3.8 mmol/L were investigated. RESULTS: The rates of achieving targets for HbA1c, blood pressure, and lipids were 52.9%, 46.8% and 65.5%, respectively. The prevalence of microvascular complications was ∼28% each, 6.4% of which had all microvascular complications, while that of macrovascular complications was 12.6%. With an increasing duration of diabetes, the rate of achieving target HbA1c decreased and the prevalence of each complication increased despite increased use of diabetes medication. The prevalence of each complication decreased according to the number achieving the 3 treatment targets and was lower in subjects without macrovascular complications than those with. Adjustments for considerable covariates exhibited that each complication was closely inter-related, and the achievement of each target was significantly associated with being free of each complication. CONCLUSIONS: Almost half of the subjects examined did not meet the recommended targets. The risk of each complication was significantly affected by 1 on-target treatment (inversely) and the concomitance of another complication (directly). Total diabetes care including one-by-one management of modifiable risk factors and complications may be important for high-quality care. The future studies including more subjects and clinics with precise complication status are needed.